2017
DOI: 10.1186/s40793-017-0230-x
|View full text |Cite
|
Sign up to set email alerts
|

High quality draft genome sequence of Janthinobacterium psychrotolerans sp. nov., isolated from a frozen freshwater pond

Abstract: Strain S3-2T, isolated from sediment of a frozen freshwater pond, shares 99% 16S rRNA gene sequence identity with strains of the genus Janthinobacterium. Strain S3-2T is a facultative anaerobe that lacks the ability to produce violacein but shows antibiotic resistance, psychrotolerance, incomplete denitrification, and fermentation. The draft genome of strain S3-2T has a size of ~5.8 Mbp and contains 5,297 genes, including 115 RNA genes. Based on the phenotypic properties of the strain, the low in silico DNA-DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Both the values qualify above the cut-off value for species boundary [ 33 , 34 ], and hence the results were consistent with the MLSA clustering of strain ERGS5:01 with PAMC 25724. In a recent study, strain PAMC 25724 has been reported as the strain of the species J. lividum [ 35 ] and is a validly published species with the availability of culture at Polar and Alpine Microbial Collection with accession number 25724. In another study, strains HH100, HH102, HH103, HH104, HH106, HH107, and 5059B had shown to be clustered together in proximity to J. lividum DSM 1522 [ 6 ].…”
Section: Insights From the Genome Sequence And Comparative Genomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the values qualify above the cut-off value for species boundary [ 33 , 34 ], and hence the results were consistent with the MLSA clustering of strain ERGS5:01 with PAMC 25724. In a recent study, strain PAMC 25724 has been reported as the strain of the species J. lividum [ 35 ] and is a validly published species with the availability of culture at Polar and Alpine Microbial Collection with accession number 25724. In another study, strains HH100, HH102, HH103, HH104, HH106, HH107, and 5059B had shown to be clustered together in proximity to J. lividum DSM 1522 [ 6 ].…”
Section: Insights From the Genome Sequence And Comparative Genomicsmentioning
confidence: 99%
“…Comparative genomic study was performed to reveal the genomic diversity across the genus Janthinobacterium . Genome data included J. agaricidamnosum DSM9628 (HG322949, [ 36 ]); J. psychotolerans S3–2 (LOCQ00000000, [ 35 ]) and J. lividum with multiple strains of Marseille (CP000269; [ 37 ]); Ant5–2 (LNCE00000000, [ 38 ]); PAMC 25724 (AHHB00000000, [ 2 ]; CG3 (APFF00000000, [ 39 ]); HH01 (NZ_AMWD00000000, [ 40 ]); RIT308 (JFYR00000000, [ 41 ]); MTR (JRRH00000000, [ 42 ]);RA13 (JQNP01000001, [ 43 ]); KBS0711 (LBCO00000000, [ 44 ]); CG23_2 (CYSS00000000, [ 45 ]); DSM1522 (LRHW00000000), MP5059B (LRHX00000000), HH100 (LRHY00000000), HH102 (LRHZ00000000), HH103 (LRIA00000000), HH104 (LRIB00000000), HH106 (LRIC00000000), and HH107 (LRID00000000) [ 4 ]. Few other genome sequence were retrieved from Gold database or IMG [ 22 , 23 ]: J. lividum strain NFR18 (FPKH00000000); Janthinobacterium sp.…”
Section: Insights From the Genome Sequence And Comparative Genomicsmentioning
confidence: 99%
“…Unexpectedly, the vioABCDE operon, which contains the genes responsible for the synthesis of the violacein pigment, was not found in the genome, but some species are not considered to have this gene set ( 9 ). The genome shows several enzymes involved in denitrification processes.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Pseudomonas was responsible for chronic infection [ 47 ] and was the most common bacteria in the soil [ 48 ], and this may explain why the relative abundances of Pseudomonas in dry soil sample were higher than those in water and wet soil samples. Janthinobacterium may cause a soft rot disease of Agaricus bisporus [ 49 ] and were isolated from both water [ 50 ] and soil [ 51 ]; however, there were no such genus in the soil samples of this study.…”
Section: Discussionmentioning
confidence: 98%